Consumer Perception Of Aromatherapy In Malaysia - Chin, Kee Leong (2007)
The main objective of this study i sto find out the overall perception of consumers towards aromatherapy in Malaysia, which will relate to their experince(if any) , and their knowledge and awareness of its application.